Proceedings of the 8th Annual Conference on Genetic and Evolutionary Computation 2006
DOI: 10.1145/1143997.1144199
|View full text |Cite
|
Sign up to set email alerts
|

Selecting for evolvable representations

Abstract: Evolutionary algorithms tend to produce solutions that are not evolvable: Although current fitness may be high, further search is impeded as the effects of mutation and crossover become increasingly detrimental. In nature, in addition to having high fitness, organisms have evolvable genomes: phenotypic variation resulting from random mutation is structured and robust. Evolvability is important because it allows the population to produce meaningful variation, leading to efficient search. However, because evolva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 27 publications
0
28
0
1
Order By: Relevance
“…Previous studies have indicated that temporally varying environments can affect several properties of evolved systems such as their structure (6), robustness (21), evolvability (22,23), and genotype-phenotype mapping (10,24). In particular, goals that change over time in a modular fashion (18), such that each new goal shares some of the subproblems with the previous goal, were found to spontaneously generate systems with modular structure (18).…”
mentioning
confidence: 99%
“…Previous studies have indicated that temporally varying environments can affect several properties of evolved systems such as their structure (6), robustness (21), evolvability (22,23), and genotype-phenotype mapping (10,24). In particular, goals that change over time in a modular fashion (18), such that each new goal shares some of the subproblems with the previous goal, were found to spontaneously generate systems with modular structure (18).…”
mentioning
confidence: 99%
“…Such motif significance profiles are typical of neural networks found in nature [13]. Such highly recurrent network structures may be used to increase the detectability of mutations affecting evolvability [18].…”
Section: Network Motifsmentioning
confidence: 89%
“…One possible reason is that with the implicit encoding, evolution controls how the phenotypes are distributed, thereby transforming random mutations into structured phenotypic variation. Furthermore, since such mutations have an immediate and detectable impact on fitness, fewer mutations are required on average to create a gradient for selection [18].…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Thus, high evolvability can be detected and favored by such selection pressure. For an artificial evolutionary system Reisinger et al concur when they propose an indirect encoding representation to improve evolvability [56,57]. A gradually changing fitness function Journal of Artificial Evolution and Applications 3 is designed to measure evolvability of representations and to evolve a population that is adaptive under different environments.…”
Section: Definitionmentioning
confidence: 99%
“…They are sensitive to training data and to varying constraints of different models; so a common framework would be required. Moreover, Reisinger and Miikkulainen [56] propose an evolvable representation and an evaluation strategy to exert indirect selection pressure on evolvability. In their work, a systematically changing fitness function is adopted according to a special evolvable representation that can reflect efficiently how genetic changes restructure phenotypic variation.…”
Section: Definitionmentioning
confidence: 99%